Academic Inbreeding: Pro and Contra - Sivak, Elizaveta; Yudkevich, Maria (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The article discusses the positive and negative effects of colleges’ practice of hiring their own alumni. The authors review empirical research that analyzes the prevalence and effect of this phenomenon in various educational systems, and the difference in the behavior between insiders and outsiders. To illustrate the ‘upbringing phenomenon’ characteristic of Russian universities, the authors use data collected in interviewing teachers and department heads from 28 faculties of universities in St. Petersburg. All these faculties award degrees in economics. The article investigates how the colleges’ policy of hiring their own alumni affects the strategies and values of university teachers.